Regulation of signaling pathways by tanshinones in different cancers - Lin, X.; Qureshi, M. Z.; Romero, M. A.; Khalid, S.; Aras, A.; Ozbey, U.; Farooqi, A. A. (Cellular and Molecular Biology, 2017)
Past several years have witnessed dramatic leaps in our understanding of rewiring of gene expression at the translation level during cancer developmentthat provides linchpin support to the transformed phenotype. Most recent and ground-breaking developments in the field of molecular oncology aredriven by an explosion in technological advancements and have started to reveal previously unimagined regulatory mechanisms and how they intricately co-ordinate to modulate cancer progression, loss of apoptosis and development of resistance against different therapeutics. However, the insights gained from work in this natural product research have far-reaching impact because of rapidly increasing repertoire of medicinally and biologically efficient phytochemicals. How Tanshinones mediate targeting of JAK-STAT, ER stress associated signaling cascade,PI3K/AKT/mTOR pathway,autophagy, TRAIL pathway and microRNAs are being discovered and will prove to be helpful in getting a step closer to personalized medicine.